Incidence and Outcomes of Hypernatremia in Adult Neurological Non–Brain-Dead Patients Admitted to Tertiary Care Neurologic Institute: A Retrospective Study - Jena, Sritam S.; Venkatapura, Ramesh J.; Christopher, Rita; Shukla, Dhaval; Chakrabarti, Dhritiman (Journal of Neuroanaesthesiology and Critical Care, 2019)
Background Hypernatremia is known to have high mortality and morbidity in patients with neurological disorders. However, in most studies, it is not clear whether hypernatremia associated with brain death has been excluded. Including brain-dead patients will spuriously give a very high mortality rate. Therefore, in this study, we have evaluated the mortality of hypernatremic patients after excluding the brain-dead patients on the first day of hypernatremia.Methods All neurological patients admitted to the hospital who developed hypernatremia (serum Na > 150 mEq/L) were included in the study. Brain-dead patients and patients with Glasgow coma score (GCS) 3 on the first day of detection of hypernatremia were excluded. Demographic variables, clinical variables, and outcome variables were collected from the case files retrospectively.Results In total, 100 patients developed hypernatremia during the study period. Among them, 14 patients were excluded because of GCS 3 or unavailability of GCS data on the day of detection of hypernatremia. There were 37 mild, 28 moderate, and 21 severe hypernatremic patients. The mortality was 32%, 39%, and 52% in the mild, moderate, and severe hypernatremic patients, respectively. Patients with traumatic brain injury had higher mortality in comparison to all other disease conditions (56% vs. 29.6%, p < 0.02).Conclusion The mortality is high even in mild cases of hypernatremia. Very high mortality (52%) is seen in severe hypernatremic patients. Therefore, it is important to monitor, identify, and treat these patients aggressively.
Keywords: head injury; hypernatremia; mortality; sodium disturbance